Iron Deficiency Anaemia in Children - Obeagu, Emmanuel Ifeanyi; Obeagu, Getrude Uzoma; Habimana, Jean Bosco (International Research in Medical and Health Sciences, 2023)
Two-thirds of anemia in children worldwide, of which IDA accounts for 20 to 25% of cases, are caused by iron deficiency, which is a significant global health burden. Despite treatment, unfortunately, IDA can have neuropsychiatric effects and is strongly associated with cognitive decline throughout childhood and adolescence 60% of African children under 5 years of age are anemic, of which IDA accounts for 50% of the burden. However, iron salt supplementation has a significant impact on preventing or reducing anemia. It is estimated that since the late 1990s, about 2 billion people worldwide have ID disease, which causes half of all anemia cases. The majority of people with iron deficiency who do not have anemia have no symptoms and can only be identified by a screening test. The most common symptom of iron deficiency anemia is pallor, also commonly seen in the nail bed, conjunctiva, palmar crease, and nail bed. In the absence of iron and ferritin studies, haemoglobin can be a sensitive test to distinguish IDA from other forms of microcytic anemia.
Keywords: Children; Iron; Iron Deficiency Anaemia; Nutrients